An exploratory study of the experiences of student support officers offering counselling services to students at TVET Colleges in the Western Cape - Naidoo, Sashen (Department of Psychology, 2025)
This study explored the experiences of student support officers (SSOs) who offer counselling services to students at Technical and Vocational Education and Training (TVET) colleges in the Western Cape province, South Africa. Methodologically, the study employs a phenomenological approach as its focus is on experience-generated knowledge. It is thus located within the qualitative paradigm to give voice and the perspectives of the SSOs. Previous literature demonstrates that students historically sought counselling primarily for academic and career purposes. However, over time, the nature and type of counselling students required became increasingly complex with greater expectations of counsellors at higher education institutions. Therefore, further research is necessary to better understand this consequential phenomenon from the perspective of the SSOs through their meaning-making. This study found that SSOs experienced their role to be ill-defined, fluid and riddled with challenges of language and culture thus affecting the quality of meaningful counselling. This study offers recommendations emanating from interviews with SSOs. This study is germane to governance in TVET colleges in the Western Cape but may offer insights to other institutions of higher learning.